Disposition of inorganic mercury in pregnant rats and their offspring. (1st September 2015) - Oliveira, Cláudia S.; Joshee, Lucy; Zalups, Rudolfs K.; Pereira, Maria E.; Bridges, Christy C.
Highlights: Inorganic mercury (Hg 2+ ) is taken up by the placenta and by fetal tissues. Hg 2+ accumulation in fetal organs is dependent upon maternal dose. Acute renal injury in dams may alter the pool of Hg 2+ in other organs. Abstract: Environmental toxicants such as methylmercury have been shown to negatively impact fetal health. Despite the prevalence of inorganic mercury (Hg 2+ ) in the environment and the ability of methylmercury to biotransform into Hg 2+, little is known about the ability of Hg 2+ to cross the placenta into fetal tissues. Therefore, it is important to understand the handing and disposition of Hg 2+ in the reproductive system. The purpose of the current study was to assess the disposition and transport of Hg 2+ in placental and fetal tissues, and to test the hypothesis that acute renal injury in dams can alter the accumulation of Hg 2+ in fetal tissues. Pregnant Wistar rats were injected intravenously with 0.5 or 2.5 μmol kg −1 HgCl2 for 6 or 48 h and the disposition of Hg 2+ was measured. Accumulation of Hg 2+ in the placenta was rapid and dose-dependent. Very little Hg 2+ was eliminated during the initial 48 h after exposure. When dams were exposed to the low dose of HgCl2, fetal accumulation of Hg 2+ increased between 6 h and 48 h, while at the higher dose, accumulation was similar at each time point. Within fetal organs, the greatest concentration of Hg 2+ (nmol/g) was localized in the kidneys, followed by the liver and brain. A dose-dependent increase in the accumulation of Hg 2+ in fetal organs was observed, suggesting that continued maternal exposure may lead to increased fetal exposure. Taken together, these data indicate that Hg 2+ is capable of crossing the placenta and gaining access to fetal organs in a dose-dependent manner.